High cholesterol diet activates ER stress mediated apoptosis in testes tissue: Role of alpha-tocopherol - SÖZEN, AHMET ERDİ; ERCAN, FERİHA; KARTAL ÖZER, NESRİN (WILEY, 2022)
The seminiferous tubules where spermatogenesis occurs are enveloped and protected by the Sertoli cells to support germ cells undergoing meiosis to produce haploid gametes. Clearly, induction of apoptosis in seminiferous tubules leads to abnormalities in spermatogenesis and male infertility. Studies demonstrated that increased hyperlipidemia impairs male infertility and spermatogenesis by enhancing seminiferous tubules apoptosis. However, molecular mechanisms underlying high-cholesterol-mediated testicular damage remain poorly elucidated. In this scope, we established a rabbit model and investigated the role of endoplasmic reticulum (ER) stress on high cholesterol diet induced seminiferous tubule apoptosis. Histopatological examinations revealed increased seminifer tubule apoptosis in testes of rabbits fed high cholesterol diet. In addition, phosphorylated forms of IRE1 and PERK, two well-identified markers of ER stress, were significantly induced in accordance with high cholesterol diet. High cholesterol diet also exhibited CHOP induction in testes, indicating increased ER stress related apoptosis. Supplementation of alpha-tocopherol significantly attenuated cholesterol mediated ER stress, and restored seminiferous tubules apoptosis. Taken together, our findings suggest that alpha-tocopherol might be capable to reduce testicular damage via ameliorating histopatological features and inhibiting seminiferous tubules apoptosis in hypercholesterolemic rabbits.
Keywords: apoptosis; endoplasmic reticulum stress; hypercholesterolemia; seminiferous tubule; alpha-tocopherol; ENDOPLASMIC-RETICULUM STRESS; TESTICULAR STEROIDOGENESIS; REPRODUCTIVE FUNCTION; OXIDATIVE STRESS; SERTOLI-CELLS; SEMEN QUALITY; VITAMIN-E; SPERM; BLOOD; ACID